"This Is Not Representation!": A Study of Urbanization, Alienation, and Tolerance Through a Vietnamese Heritage Language and Culture Program. (March 2017) - Nguyễn, Thu Sương Thị; Anderson, Jantina
This case centers on a Vietnamese language and culture program situated within an urban context. It illustrates how sociohistorical and geopolitical contexts interplay in understanding relations within schools as well as school–community relations. A new ethnoburb creates both opportunities and challenges for the Vietnamese community related to cross-ethnic dynamics and the way interactions are shaped bureaucratically, socially, and politically. Increasing proximity of differences produced through processes of urbanization provides opportunity for school and community leaders to examine mechanisms (assumptions about difference, bureaucratic expedience, socio-political power, notions of "natural" social hierarchies, etc.) by which in/tolerance and alienation are produced.